2011
DOI: 10.1016/s0924-9338(11)72153-8
|View full text |Cite
|
Sign up to set email alerts
|

Basic psychological needs, culture and well-being: A comparison of turkish immigrant and German women in Germany

Abstract: IntroductionSelf-determination theory posits that autonomy and relatedness are innate and universal psychological needs and that when satisfied well-being is enhanced. Contrarily, some cross-cultural perspectives suggest that the degree of autonomy and relatedness satisfaction necessary for well-being within a particular society is mediated by cultural orientations.ObjectiveGiven the existing debates on cultural universality of basic needs, we examined the influence of culture on the relationship between basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus far, the cultural differences on the basic psychological needs are mainly reflected in two dimensions: (1) The level of perceived satisfaction of needs (e.g., Chirkov et al, 2005 ; Church et al, 2013 ); (2) assessment of the importance of the needs, especially with respect to PWB (e.g., Hahn and Oishi, 2006 ; Wang et al, 2007 ; Balkir et al, 2011 ). Specifically, a study conducted by Church et al ( 2013 ) found that Asian participants (Japan, China, Malaysia, and the Philippines) averaged lower than non-Asian participants (U.S., Mexico, and Venezuela) in perceived satisfaction of autonomy and competence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, the cultural differences on the basic psychological needs are mainly reflected in two dimensions: (1) The level of perceived satisfaction of needs (e.g., Chirkov et al, 2005 ; Church et al, 2013 ); (2) assessment of the importance of the needs, especially with respect to PWB (e.g., Hahn and Oishi, 2006 ; Wang et al, 2007 ; Balkir et al, 2011 ). Specifically, a study conducted by Church et al ( 2013 ) found that Asian participants (Japan, China, Malaysia, and the Philippines) averaged lower than non-Asian participants (U.S., Mexico, and Venezuela) in perceived satisfaction of autonomy and competence.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies have shown cultural differences in the strength of the relationship between basic psychological needs satisfaction and PWB, which were also more consistent with the cross-cultural perspective. Balkir et al ( 2011 ) found that German women's (individualistic cultures) well-being was positively associated with autonomy satisfaction but not with relatedness satisfaction. Conversely, Turkish women's (collectivist cultures) well-being was positively associated with relatedness satisfaction but not with autonomy satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many experts and scholars at home and abroad have studied cultural creative works from different perspectives, and compared with the European and American countries, China still has a big gap in the study of cultural creative works. Foreign art and cultural creative works well reflect the transmission of cultural significance and the regional characteristics (Balkir, Arens, & Barnow, 2011), while Chinese art and cultural creative works are faced with serious similarities and fail to get enough attention.…”
Section: Introductionmentioning
confidence: 99%